Collapse : a novel - Louis, Édouard (Farrar, Straus and Giroux, 2026)
"From "one of the most important, politically vital and morally bracing writers of his generation" (The Guardian), an unflinching account of Édouard Louis's brother's life and death"-- Provided by publisher.